PENGARUH PEMBANGUNAN PERKEBUNAN TERHADAP KESEJAHTERAAN MASYARAKAT DI KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Afrila Afrila; Almasdi Syahza; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrak: This research is motivated by the dominant low education of farmers. The purpose of this study was to determine the influence of plantation development on the welfare of the community in Rambah Hilir District, Rokan Hulu Regency. The population in this study were farmers in Rambah Hilir District, Rokan Hulu Regency, consisting of 150 farmers who chose samples using the Slovin formula to produce 60 samples. In collecting data, namely by interviewing and distributing questionnaires with research instruments. Furthermore, to analyze the data using the chi-square test. When viewed from the results of statistical analysis with the chi-square test, it can be seen that Asymp. Sig. (2 sides) 0.000. This value is less than 0.05. So it can be concluded that there is an effect of plantation development on the welfare of the community in Rambah Hlir District, Rokan Hulu Regency.Key Words: Education, Price, Farmers' Income, Chi-Square Test